Immune Thrombocytopenic Purpura (ITP) as an Uncommon Extraintestinal Complication of Crohn’s Disease: Case Vignette and Systematic Literature Review - Raisa Epistola; Tiffanie Do; Ritika Vankina; Daniel Wu; James Yeh; Michael W. Fleischman; Jennifer M. Lee (Case Reports in Hematology)
While the association of immune thrombocytopenic purpura (ITP) and inflammatory bowel disease (IBD) has been described in a few case reports, management of ITP as an extraintestinal manifestation of Crohn’s disease (CD) is less studied. There are approximately a dozen cases describing the management of patients dually diagnosed with CD/ITP. Previous reports postulated that the mechanism of ITP in CD was through the presence of circulating immune complexes in the serum and antigenic mimicry due to increased mucosal permeability in active colitis, versus increased mucosal production of TH1-type proinflammatory cytokines during CD flares, which may account for remission of ITP with surgery for CD. We present a case of a 27-year-old man who presented with medically refractory CD and ITP who responded to surgical management with colectomy and splenectomy, along with a systematic review of the literature. These cases suggest that colectomy should be considered in the treatment of medically refractory ITP among patients with concomitant CD.